2016
DOI: 10.1063/1.4964902
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and accurate evaluation of potential energy matrix elements for quantum dynamics using Gaussian process regression

Abstract: A compact and accurate semi-global potential energy surface for malonaldehyde from constrained least squares regression The Journal of Chemical Physics 141, 144310 (2014); 10.1063/1.4897486Gaussian process regression to accelerate geometry optimizations relying on numerical differentiation The Journal of Chemical Physics 148, 241704 (2018); 10.1063/1.5009347 THE JOURNAL OF CHEMICAL PHYSICS 145, 174112 (2016) Efficient and accurate evaluation of potential energy matrix elements for quantum dynamics using Gau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 88 publications
0
55
0
Order By: Relevance
“…This subset is defined by the choice of DVR and it is the configuration subspace defined by this selection in which the GPR approximation 180 of the PES is constructed. With regards to the GPR, we note that we used α=0.5 in all simulations reported here (see equation (5)); earlier work has shown that variation of this parameter within a reasonable range should give give little overall 185 change in the results presented below [38].…”
Section: Methodsmentioning
confidence: 99%
“…This subset is defined by the choice of DVR and it is the configuration subspace defined by this selection in which the GPR approximation 180 of the PES is constructed. With regards to the GPR, we note that we used α=0.5 in all simulations reported here (see equation (5)); earlier work has shown that variation of this parameter within a reasonable range should give give little overall 185 change in the results presented below [38].…”
Section: Methodsmentioning
confidence: 99%
“…One can then Taylor expand the electronic energy and/or nonadiabatic coupling about this centroid and evaluate the resulting integral analytically. 113,127,[139][140] As an example, we consider the expansion of the intrastate coupling term -containing the electronic energybetween two TBFs k and i with centroid position R ki…”
Section: Ab Initio Multiple Spawningmentioning
confidence: 99%
“…31,37 Since the Hessians are not needed for the propagation of the classical trajectory, additional speed-up is achieved through parallel computation of the Hessians after the full trajectory is known. Note that other Hessian approximations, such as the Hessian update schemes [38][39][40] and Gaussian process regression 41,42 have been developed in the context of ab initio simulations. The considerable cost of multiple Hessian evaluations has also inspired various semiclassical approximations, 43 including the prefactor-free, 22 adiabatic, 44,45 harmonic, 43 and "poor person's" 46 variations of the Herman-Kluk propagator.…”
Section: Hessian Interpolationmentioning
confidence: 99%